Digital Media And The Amplification Of Marginalised Voices In Select Communities In Akwa Ibom State - George Nathan Brown; Morah Doris Ngozi, PhD; Ifeanyi Martins Nwokeocha, PhD; Christian Ugochukwu EGEH; Promise Adaku Obi (International Journal of Technology and Education Research, 2025)
This study investigated the potential of using digital media to amplify marginalised voices in select communities in Akwa Ibom State, Nigeria. The objectives were to examine the extent to which digital media amplifies marginalised voices, identify the challenges faced by marginalised groups in utilising digital media, and explore strategies for enhancing the use of digital media to promote marginalised voices. The study was anchored on the Social Identity Theory and Technological Acceptance Model. The study adopted a survey research design, with a sample size of 399 respondents selected using Taro Yamane's formula. Data analysis revealed that 37% of respondents indicated that digital media "often" amplifies marginalised voices, while 26% faced obstacles related to online harassment and cyberbullying, and 25% lacked digital literacy skills. The study also found that digital literacy training programmes (23%) and access to digital devices (23%) were paramount strategies for enhancing the use of digital media. The study concludes that digital media has the potential to amplify marginalised voices, but its effectiveness is hindered by challenges, highlighting the need for targeted interventions. Recommendations include prioritising inclusivity and accessibility features on digital media platforms, implementing digital literacy training programmes and online safety measures, and providing access to digital devices, affordable internet data plans, and digital literacy training programs to promote digital inclusion and empowerment among marginalised groups.